Tapak Tilas Akuntansi Syariah - Windari, Windari (Institut Agama Islam Negeri Padangsidimpuan, 2016)
In Islamic accounting there are three values or principles of accounting that had been accepted. They are responsibility, justice and general truth, that always fullfil in islamic accounting system. Those three values have been being a basic operational principle, especially in sharia banks. Therefore, those three values have to be practiced in real life by all islamic bankers.